Respiratory symptoms, pulmonary function and allergy to fur animals among fur farmers and fur garment workers - Uitti, Jukka; Nordman, Henrik; Halmepuro, L.; Savolainen, J. (Scandinavian Journal of Work, Environment & Health, 1997)
' ' OBJECTIVES ': 'This study determined the prevalence of respiratory symptoms and immediate hypersensitivity to fur allergens among fur farmers and fur garment workers and measured the pulmonary function of these groups of workers. Methods Fur farmers (N=188) and fur garment workers (N=175) were compared with workers in a factory producing polyvinyl products (N=181) and bank and health center workers (N=118), respectively. The groups were given a self-administered questionnaire, lung function tests (spirometry, diffusing capacity), and skin prick tests to common environmental allergens, and epithelium (hair) and urine of fur animals. ResultsRhinitis symptoms and eye complaints were significantly more common among the fur garment workers than among their referents, but were not associated with atopy. Between the fur farmers and their referents, the symptom prevalence did not differ significantly. Smoking explained the lower forced vital capacity and forced expiratory volume in 1 second of the fur garment workers. The prevalence of positive skin tests did not differ significantly between the exposed group and their respective referents. The skin tests showed cross-reactivity between antibodies to fur and domestic animal allergens. As confirmed by a questionnaire sent to former fur workers, selection took place for both groups of fur workers. ConclusionsFur garment workers have an excess of rhinitis and eye symptoms, which primarily appear to be nonimmunologic. Allergy to fur animals forces sensitized workers, especially asthmatics, to leave the trade. A supplementary questionnaire to former workers on pertinent exposures and reasons for leaving a particular job can be recommended for use in prevalence studies.
Keywords: cross-reactivity; domestic animal allergens; former worker; fur animal allergens; questionnaire; respiratory disorder; skin prick test